R. Gupta's Joint CSIR- UGC (NET) Life Science (Part B & C) Exam Guide - Ritambhara Singh (Ramesh Publishing House, 2018)
This comprehensive book is useful for Joint CSIR-UGC (NET) : Life Science (Part B & C) Examination. This book included Study Material & Previous Years' Papers for the purpose of practice of questions based on the latest pattern of the examination. Detailed Explanatory Answers have also been provided for the selected questions for Better Understanding of the Candidates.